COST ACCOUNTING AND PRICING POLICIES. - Devine, Carl Thomas (The Accounting Review, 1950)
There is abundant evidence that the cost accountant's traditional approach has been strongly influenced by classical and neo-classical economic theory. With the possible exception of specific order industries the general prescription that management should concentrate on those items which yield the largest markup is based squarely on the assumption of pure competition. Clearly in pure or near pure competition with unlimited demand for the firm's products at going prices management is well advised to push- in a production sense-those items which yield the largest markup. The extension of this prescription to products to be sold in areas of imperfect competition seems to be just as dearly unwarranted. Businessmen and accountants, particularly, have often argued that production and distribution cost accounting gives the key to decisions as to which lines, products, territories, etc should be pushed through increased advertising expenditures and other sales pressure. The fact that sales effort is necessary is an indication that the products are differentiated and that the demand for each product is not completely elastic. Intelligent pricing and sales-pressure decisions must give full consideration to estimates of demand elasticities and to the probable reaction of demand schedules to changes in (and different types of) advertising and other selling methods.